Home Inotropes in Patients Supported with Left Ventricular Assist Devices. Issue 1 (January 2019) - Anyanwu, Emeka C.; Kagan, Viktoriya; Bhatia, Ankit; Tehrani, David M.; Adatya, Sirtaz; Kim, Gene; Sarswat, Nitasha; Jeevanandam, Valluvan; Sayer, Gabriel; Uriel, Nir
Abstract : There is little data outlining the use of outpatient inotropic medications in patients with existing left ventricular assist devices (LVADs). This case series explores this patient population and seeks to define the indications, complications, and safety of dual support. A retrospective chart review was conducted for all patients on LVAD and then subsequently started on home inotropes post device implant. Eight patients met inclusion criteria. The indications for inotropes were right ventricular failure, aortic insufficiency with biventricular failure, LVAD thrombosis with contraindication to device exchange, and cannula malposition with elevated pulmonary vascular resistance. Mean duration of combined support was 273 ± 170 days. Cardiac index improved from 1.96 ± 0.24 to 2.31 ± 0.35 L/min/m 2 after inotropes ( p = 0.02). There was no change in hospital admissions. The most common reason for readmission was heart failure symptoms, followed by bleeding. Five patients died during the study period, one underwent heart transplant, and two remain on inotropic support. Home inotropes may be indicated in selected continuous flow left ventricular assist device (CF-LVAD) patients with refractory right ventricular failure or impaired LVAD function. Inotropes can improve hemodynamics and provide palliation of symptoms. However, long-term inotrope use does not reduce hospital readmissions and is associated with multiple complications related to the need for an indwelling intravenous line. Abstract : Supplemental Digital Content is available in the text.